Analysis of the Influence of the Certified Independent Study Internship (MSIB) and the Independent Student Exchange (PMM) Programs under MBKM on Students’ Work Readiness - Yuli Yuli; Endah Dewi Purnamasari; Emilda Emilda (STIE Amkop Makassar, 2026)
This study aims to analyze the influence of the Certified Independent Study Internship Program (MBKM) and the Independent Student Exchange Program on student job readiness, focusing on MBKM students who have participated in the Certified Independent Study Internship Program and the Independent Student Exchange Program. The research method used a quantitative approach, with the study population being students from the two MBKM programs. The research sample consisted of 98 respondents selected through probability sampling techniques. Data obtained in this study used observation and questionnaires. Multiple linear regression analysis techniques were used, using SPSS version 25 software. Data testing included validity tests, reliability tests, and tests of classical assumptions such as normality, heteroscedasticity, and multicollinearity. The results showed that partially, the Certified Independent Study Internship (MSIB) and the Independent Student Exchange (PMM) variables each had a positive and significant effect on student job readiness. Simultaneously, both variables had a positive and significant effect on student job readiness. This study explains that the MBKM Program, namely the Certified Independent Study Internship (MSIB) and the Independent Student Exchange (PMM), can be key factors in student job readiness, especially for MBKM program students.